The Correlation between Compensation and Career Development with Job Satisfaction of Inpatient Nurses: A Study in a Hospital in Jakarta - Abdul Aziz; Rosidawati Batubara (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Working in a workplace or organization for a short or long time can lead to job satisfaction which will directly or indirectly have a good impact on work. Nurse job satisfaction is very important for the realization of high loyalty to work and the organization in carrying out daily tasks in hospitals or other health services. Various factors can increase job satisfaction in various fields of work including the field of nursing. These factors include compensation and career development. The type of research conducted was a correlational research method with a cross sectional approach. This correlation test was carried out between compensation and career development and job satisfaction of nurses at X Hospital. Correlation test with linear regression test from the results of questionnaire answers from 25 nurses who were research respondents . The results showed that there was a positive correlation between the two dependent variables (compensation and career development) with job satisfaction with a value of p = 0.000 and the partial analysis obtained a value of p = 0.000 for compensation and p = 0.027 for career development. Based on the above results of the two factors, compensation is a factor that has a stronger influence on nurse job satisfaction when compared to career development factors. For this reason, it is expected that hospital leaders can develop a good compensation system in their management.